Peran Taman Sekolah sebagai Motivasi Siswa SD dalam Mencintai Tumbuhan Dan Alam Sekitar - Ramadaniyanti, Dewi Putri; Umam, Khoirul; Alfayed, Dody; Siswoyo, Andika Adinanda (Pendagogia: Jurnal Pendidikan Dasar, 2023)
The school garden is one of the facilities and infrastructure found in the school environment. School gardening has several benefits, for schools, namely to beautify the school environment and give a feeling of coolness, because it is surrounded by beautiful plants. School gardens can motivate students to study because with a beautiful and cool school environment, they will feel at home and eager to learn. The purpose of this research is to explain the role of the school garden as a motivation to love plants and the natural surroundings. In this study the method used is a qualitative method. In this study the subjects used were grade 1 UPTD SDN Kamal 1 students with a total of 33 students. The data collection technique used in this study was direct observation and documentation. The data analysis technique used is data reduction, data presentation and conclusion. The analysis technique used is in accordance with the type of research that is taken, namely qualitative. Tamanization is an activity that provides facilities to support the learning process for students. School gardening has several benefits, for schools, namely to beautify the school environment and give a feeling of coolness, because it is surrounded by beautiful plants. School gardens can motivate students to study because with a beautiful and cool school environment, they will feel at home and eager to learn.